PWE-010 Dietary campesterol is inversely associated with the risk of developing oesophageal adenocarcinoma: a UK prospective study in the EPIC-Norfolk cohort, using information from 7-day food diaries. (28th May 2012) - Alexandre, L; Yates, M; Luben, R; Cheong, E; Igali, L; Fitzgerald, R; Khaw, K-T; Hart, A
Abstract : Introduction: Dietary phytosterols (PS), including campesterol, the most bioavailable of this group, are structurally similar to cholesterol, and are present in grain legumes, cereals, nuts and vegetable oils. Experimental studies have shown PS have several anticarcinogenic effects, including inducing apoptosis and inhibiting both angiogenesis and cell proliferation. The aim of this study was to conduct the first epidemiological investigation to determine if an inverse association exists between PS intake and the risk of both Barrett's oesophagus (BO) and oesophageal adenocarcinoma (OAC). Methods: A total of 25 639 men and women aged 40–75 years, were recruited between the years 1993 and 1997 into the European Prospective Investigation into Cancer (EPIC)-Norfolk cohort Study. At baseline, participants completed detailed 7-day food diaries which were coded by nutritionists. Subjects were followed-up over subsequent years for the development of BO and OAC. A review of case notes confirmed these diagnoses. Dietary intakes were compared between cases and a random sample of 3 797 controls in a case-cohort analysis. Cox regression estimated the HR for both campesterol and total PS. Results: During follow-up, 104 patients were diagnosed with BO (80% men, median age 67.0 yrs [IQR 61.1–73.1] at diagnosis) after a median follow-up of 6.2 yrs (IQR 4.1–8.1). A further 63 patients developed OAC (83% men, median age 73.0 yrs [IQR 67.0–78.0] at diagnosis) after a median follow-up of 6.4 yrs (IQR 4.4–8.9). For BO, no significant associations were found with campesterol (HR 1.47, 95% CI 0.77 to 2.79) or total dietary PS (HR 1.28, 95% CI 0.70 to 2.33), in either sex. For OAC, in men, there were inverse associations with campesterol (HR 0.43, 95% CI 0.22 to 0.83, p=0.01), in a threshold manner, comparing the lowest with a summation of the top four quintiles of intake. In women, for OAC, there were no such associations with campesterol (HR 2.13, 95% CI 0.44 to 10.15, p=0.34). Total PS intake (HR 0.71, 95% CI 0.38 to 1.35) was not significantly associated with OAC in either sex. Conclusion: Campesterol intake was associated with an approximate 55% risk reduction for OAC in men, although there were no significant effects in BO or for either condition in women. The data support a role for dietary campesterol, in preventing the malignant transformation of BO to OAC, and therefore these micronutrients should be measured in future aetiological studies of OAC. Competing interests: None declared.